Validated slab track models for railway vehicle dynamics - Thölken, Denise (2019)
Modern society demands and environmental factors are putting pressure in the development of new high speed rail networks or on the upgrade of conventional tracks to allow a significant increase in operational speeds and/or load capacity. Such requirements raise scientific and technological challenges that need to be addressed, which include the improvement of numerical tools and experimental techniques to support the design solutions. The dynamic analysis of railway systems involves multidisciplinary problems for which the most recente computer codes for rail applications only allow the study of a particular phenomenon at a time, each with its own mathematical model. By analysing such phenomena independently, it is not possible to capture all the dynamics of the complete railway system and the relevant coupling effects.